AKUMULASI PLAK DAN STATUS KESEHATAN GINGIVA PADA MURID SD DI DAERAH PENGHASIL GULA JAWA (Kajian pada Murid SDN Hargotirto, Kokap, Kulon Progo) - , RIESKI PRIHASTUTI, drg. Sri Pramestri Lastianny, MS.,Sp.Perio(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Hargotirto is a village that produce the coconut sugar. Coconut sugar contain a large amount of sucrose thats are substrate for extracellular polysaccharide synthesis that help bacterial adhesion in the dental plaque formation process. As we know, dental plaque that didnât remove can lead gingivitis. The purpose of the study was to understand dental plaque accumulation and gingival health status of the students who lived in area that produce the coconut sugar (SDN Hargotirto). The subject in this study were all of the student in SDN Hargotiro. There were 81 students examined the dental plaque accumulation and gingival health status.The data were analyzed with descriptive analysis. The result was 81,5% students had bad plaque score, 13,6% students had moderate plaque score, 2,5% students had good plaque score and 2,5% students had very good plaque score, while the gingival health status was 85,2% students had healthy gingiva and 14,8% students suffered slight gingivitis. Almost all of the students in area that produce coconut sugar had bad plaque score, while their gingival was healthy